Fra rappresentazioni concettuali, categorie grammaticali e accidenti della storia: «il fascino inquieto della ricerca scientifica» di Romano Lazzeroni (Atti del Sodalizio Glottologico Milanese, 2021)
This paper discusses the impact of Romano Lazzeroni’s scholarship on Historical Linguistics and Indo-European studies altogether, by analyzing his groundbreakingworks and long-lasting legacy in relation to the state of the art and current research on four main questions: 1. morphosyntax/semantics interface; 2. linguistic andcultural reconstruction; 3. linguistic categorization; 4. language change. A portrait of Romano Lazzeroni as a brilliant and unique Teacher is also provided, as a modest token of gratitude to a giant of science and big-hearted Mentor.
Keywords: Historical Linguistics; Morphosyntax/Semantics Interface; Linguistic Categorization; Indo-European Reconstruction; Language Change